The Arab Spring was predictable in 2007: Empirics of proof - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
We model core demands for better governance (political, economic and institutional), more employment and less consumer price inflation using a methodological innovation on the complete elimination of cross-country differences in signals susceptible of sparking social revolts. The empirical evidence based on 14 MENA countries show that the Arab Spring was predictable in 2007 to occur between January 2011 and April 2012. While the findings predict the wave of cross-country revolutions with almost mathematical precision, caveats and cautions are discussed for the scholar to understand the expositional dimensions of the empirics.
Keywords: N17; O11; O20; O47; P52; 330; Arab Spring; Political Instability; Timing; Economic Growth